THE INFLUENCE OF PERCEIVED ORGANIZATIONAL SUPPORT AND LEARNING AGILITY ON EMPLOYEE PERFORMANCE : THE MEDIATING ROLE OF WORK (A Study of Civil Servants at the Regional Secretariat of Kuningan Regency) - Retno Kurniasih; Amara Aurelia (Universitas Kuningan, 2026)
This study aims to analyze the influence of perceived organizational support and learning agility on employee performance with work engagement as a mediating variable among civil servants at the Regional Secretariat of Kuningan Regency. The research employed a quantitative survey approach involving 117 respondents selected through proportionate stratified random sampling, with data analyzed using mediation regression through the causal step method. The findings indicate that perceived organizational support and learning agility have a positive and significant effect on both work engagement and employee performance. Furthermore, work engagement positively and significantly affects performance and mediates the relationship between perceived organizational support and learning agility with employee performance. These results highlight the importance of organizational support and adaptive learning capabilities in strengthening work engagement and enhancing public sector employee performance.